Effects of bile and bile salts on growth and membrane lipid uptake by Giardia lamblia. Possible implications for pathogenesis of intestinal disease. - Farthing, M J (1985)
We have shown previously that ox and pig bile accelerate in vitro growth of Giardia lamblia. We have now investigated the possible mechanisms by which mammalian biles promote parasite growth. Growth effects of (a) ox, pig, guinea pig, and human biles, (b) pure bile salts, and (c) egg and soybean lecithins were studied in the presence of a lecithin-containing growth medium. Individually, dilute native bile and pure sodium taurocholate (TC), glycocholate (GC), and taurodeoxycholate (TDC) promoted parasite growth; growth was most marked with biles of high phospholipid content, with biles enriched in more hydrophobic bile salts (ox approximately equal to human greater than pig greater than guinea pig) and with micellar concentrations of GC and submicellar concentrations of TC and TDC. By measuring uptake of radiolabeled biliary lipids from bile and bile salt-supplemented growth medium, we showed that the parasite consumed bile lipids, with the rank order lecithin greater than bile salts. Apparent net uptake of cholesterol was considered to be due to exchange, since net loss of cholesterol from the growth medium was not detected. Although bile and bile salt-stimulated parasite growth was associated with enhanced lecithin uptake, reduction in generation time was observed at low bile and bile salt concentrations when lecithin uptake was similar to bile free controls. Thus, bile salts may stimulate Giardia growth initially by a mechanism independent of enhanced membrane phospholipid uptake. However, since Giardia has no capacity to synthesize membrane lipid, biliary lecithin may be a major source of phospholipid for growth of this parasite.